2009
DOI: 10.1007/s11926-009-0067-4
|View full text |Cite
|
Sign up to set email alerts
|

Somatosensory conflicts in complex regional pain syndrome type 1 and fibromyalgia syndrome

Abstract: The somatosensory system is an integral component of the motor control system that facilitates the recognition of location and experience of peripheral stimuli, as well as body part position and differentiation. In chronic pain, this system may be disrupted by alterations in peripheral and cortical processing. Clinical symptoms that accompany such changes can be difficult for patients to describe and health care practitioners to comprehend. Patients with chronic pain conditions such as complex regional pain sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 47 publications
1
28
0
Order By: Relevance
“…The efference copy will in part be informed by the cortical maps. In the presence of altered body perception and cortical reorganisation, where the motor and sensory maps may no longer accurately portray the actual location of body parts, then it is easy to see how a disruption in sensorimotor function may occur (see McCabe et al 2009 for review).…”
Section: The Impact Of Body Perception Disturbances and Altered Sensomentioning
confidence: 99%
See 2 more Smart Citations
“…The efference copy will in part be informed by the cortical maps. In the presence of altered body perception and cortical reorganisation, where the motor and sensory maps may no longer accurately portray the actual location of body parts, then it is easy to see how a disruption in sensorimotor function may occur (see McCabe et al 2009 for review).…”
Section: The Impact Of Body Perception Disturbances and Altered Sensomentioning
confidence: 99%
“…When this is combined with disrupted motor planning it is not surprising that those with CRPS present with high levels of anxiety and an over riding fear of touch to their affected limb. Patients often associate any increase in pain with injury, a misconception that may be detrimental to successful rehabilitation (Bruehl & Chung 2006;Rodham 2009). Similarly as progress in rehabilitation can often seem slow, patients frequently perceive they are regressing rather than progressing (Bruehl & Chung, 2006).…”
Section: Associated Parietal Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…The somatosensory system is an integral component of the motor control system that facilitates the recognition of location and experience of peripheral stimuli and body position. In chronic pain, this system may be disrupted by alterations in peripheral and cortical processing, and FM patients with chronic pain typically describe diverse alterations of the somatosensory system [29] .…”
mentioning
confidence: 99%
“…When the visual system offers limited references, the development of balance is dependent on the other two systems. Previous studies reported the effects of visual aids on balance [29] , but there is a lack of knowledge about the effects of reciprocal WBV on balance without vision in FM patients.…”
mentioning
confidence: 99%